IMPLEMENTASI RESTORATIVE JUSTICE OLEH PENYIDIK TERHADAP TINDAK PIDANA KEKERASAN DALAM RUMAH TANGGA (Studi Kasus di Kepolisian Resor Trenggalek) - Ning Imas, Dhynar Mayank; Fahrazi, Mahfudz (Universitas Islam Kadiri, 2024)
This study examines the implementation of Restorative Justice by investigators against crimes of domestic violence (a case study at the Trenggalek resort police). The purpose of this study is to analyze the implementation of regulations related to crimes of domestic violence according to the perspective of normative law and the process of Restorative Justice for crimes of domestic violence committed by investigators at the Trenggalek District Police. This research method uses empirical legal research. The results of this study explain that in general the implementation of rules related to the crime of domestic violence according to the perspective of normative law, namely that it has been regulated as a lex specialist in Law Number 23 of 2004 concerning the Elimination of Domestic Violence, explains that